Acoustic Pressure Radiated by a Circular Membrane Into the Quarter-Space - RDZANEK, Wojciech P.; SZEMELA, Krzysztof; PIECZONKA, Dawid (Archives of Acoustics, 2011)
The Neumann boundary value problem for the Helmholtz equation within the quarter-space has been considered in this paper. The Green function has been used to find the acoustic pressure amplitude as the approximation valid within the Fraunhoffer’s zone for some time-harmonic steady state processes. The low fluid loading has been assumed and the acoustic attenuation has been neglected. It has also been assumed that the vibration velocity of the acoustic particles is small as compared with the sound velocity in the gaseous medium.